A bandwidth reconfigurable antenna for devices in low UWB-applications - Mohamed Bikrat; Seddik Bri (Universitas Ahmad Dahlan, 2023)
A reconfigurable simple design planar antenna for ultra-wideband applications is proposed, with E-shaped slot contained four narrow vertical slots that has the capacity of switching using four PIN diodes with a ground plan and a microstrip power line. An additional circularly polarized (CP) band is obtained by changing the on/off states of the PIN diodes. Moreover, the four PIN diodes are attached in the middle of the E-shape slot and used to switch the radiation flow of the patch. For validation, a patch antenna design is offered, based on a distinctive situation analysis. The antenna offers the low-ultra-wideband (UWB) frequencies band. Therefore, the switch of the operating states of PIN diodes gives us a good bandwidth re-configurability. In addition, with this flexible configuration we achieve a good -10 dB bandwidths with the ability to change the bandwith ranges from narrow-band 2.3 GHz to wide-band 3.1 GHz. Also, we achieve a large band for 3 dB AR is 2.57 GHz.